(untitled) (Research, Society and Development, 2021)
Invasive cervical resorption (ICR) is an insidious, aggressive, and asymptomatic form that can lead to destruction and even loss of the dental unit. ICR is somewhat uncommon, but it can affect any tooth, with the maxillary central incisors being the most affected. Even after numerous studies, the etiology is still unclear. There are some predisposing factors, including orthodontic treatment, trauma, and internal tooth whitening, which may occur in isolation or in conjunction with each other. This article reports a clinical case of ICR class 3 with a rosy discoloration at the cervical margin and the presence of a fistula associated with a history of trauma. This suspicion was raised after radiographic examination and confirmed by cone-beam computed tomography (CBCT), with treatment via an internal approach and endodontic treatment involving debridement of the resorptive areas and filling with a bioceramic repair material and suturing. After treatment, the patient remained asymptomatic, but the fistula was no longer present. Prospective observation at 10 months showed bone formation in the middle third and well-adapted material in the cervical region, with no resorptive tissue present.